Pelaksanaan Program Literasi Sekolah Dasar di Kampar - Afrida, Lystiya Agustin; Winingsi, Kartika Rama; Rahmawati, Elsa; Khairunnas, Dimas Iqbal; Dafit, Febrina (Institut Teknologi Pendidikan Indonesia, 2023)
This article describes the literacy program for elementary school students through observation visits. Elementary school was chosen as a means of instilling literacy because it is hoped that by habituating literacy from an early age, students can acquire literacy habits as a provision for the future. The purpose of this study is to find out the process of literacy programs in elementary schools. Research is a type of descriptive research using a qualitative approach. The subjects involved in this study were school principals, teachers, students and the community at SDKampar. Collecting data in the study was carried out by interview, observation, and documentation methods. The results of the research analysis show that literacy activities are carried out by inviting students to take part in the school literacy program where all of these activities have been well attended by students even though there are some obstacles in them. There are many government policies implemented in elementary schools regarding literacy. The government is aware of the importance of literacy for elementary school students. Literacy isconsidered important because literacy will open wider insights and knowledge.